A comprehensive appraisal on status and management of remediation of DBPs by TiO2 based-photocatalysts: Insights of technology, performance and energy efficiency. (15th February 2023) - Sinha, Rupal; Ghosal, Partha Sarathi
Abstract: Disinfection has been acknowledged as an inevitable technique in water treatment. However, an inadvertent consequence of generation of carcinogenic and mutagenic disinfection byproducts (DBPs) is associated with the reaction of disinfectants and natural organic matter (NOM) present in water. More than 700 DBPs have been identified in drinking water. The conventional processes carried out in WTPs do not optimally ensure NOM elimination, which evokes the need for the incorporation of other processes. In this context, several physicochemical and advanced oxidation processes (AOP), such as adsorption, membrane techniques, photocatalysis, etc., have been studied for the removal of NOM from water. Photocatalysis using semiconductors has been one of the most proficient technologies, which utilizes light energy for the degradation of recalcitrant organics. The present study aims to provide a comprehensive appraisal on the performance of titanium dioxide (TiO2 ) based photocatalysts in the remediation of DBPs concerning the efficacy and energy requirements of the system. Furthermore, the effect of process parameters, such as pH, catalyst dose, light intensity, etc. on the efficacy of the process was also studied. It was observed that conventional P25–TiO2 powders were efficient in the degradation of dissolved organic carbon (DOC) (up to 90%). However, low photocatalytic activity under visible light activation is one of its significant downsides. Several modifications on the catalyst surface in many studies exhibited advantages, such as high humic acid (HA) degradation under visible light. Furthermore, doped TiO2 catalysts have shown high total organic carbon (TOC) degradation. The photocatalytic systems have achieved a better decrease in trihalomethane formation potential (THMFP) when compared to haloacetic acid formation potential (HAAFP). The energy requirements of the photocatalytic systems are determined by electrical energy per order (EE/O), which has been observed to be lesser for doped TiO2 and engineered TiO2 catalysts when compared with P25–TiO2 powders. Carbon, iron, silver, etc., based catalysts can be a promising alternative to TiO2 -based photocatalysts for the degradation of NOM, although further research is required in this direction. The present review provides critical highlights on the uses, opportunities, and challenges of TiO2 -based photocatalytic techniques for the management of DBPs and their precursors pertaining to an emerging area of water treatment. Graphical abstract: Image 1 Highlights: DBPs remediation involves decrease of NOM & their reduction potential Modifications over TiO2 photocatalysts increases HA degradation in visible light Doped TiO2 photocatalysts and sonocatalysis have shown high TOC removal Decrease in THMFP has been higher than HAAFP by TiO2 based photocatalysts EE/O values have been lower for doped TiO2 when compared to P25– TiO2 powder